2013
DOI: 10.1177/0363546513497926
|View full text |Cite
|
Sign up to set email alerts
|

A Prospective Randomized Study Comparing Double- and Single-Bundle Techniques for Anterior Cruciate Ligament Reconstruction

Abstract: In this prospective randomized study, the primary variable, the pivot-shift test, and other subjective and objective outcome variables revealed no significant differences between the double-bundle and single-bundle techniques at 2 years after ACL reconstruction in an unselected group of patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
68
2
2

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 67 publications
(74 citation statements)
references
References 42 publications
2
68
2
2
Order By: Relevance
“…However, in a randomized study, Ahldén et al 21 recently reported no significant differences in clinical and functional outcome when comparing single-and double-bundle ACL reconstructions. The introduction of the anatomic ACL reconstruction concept and drilling the femoral tunnel through the medial portal is most probably the reason why there has been a shift from transfixation devices to cortical fixation devices on the femoral side.…”
mentioning
confidence: 96%
“…However, in a randomized study, Ahldén et al 21 recently reported no significant differences in clinical and functional outcome when comparing single-and double-bundle ACL reconstructions. The introduction of the anatomic ACL reconstruction concept and drilling the femoral tunnel through the medial portal is most probably the reason why there has been a shift from transfixation devices to cortical fixation devices on the femoral side.…”
mentioning
confidence: 96%
“…However, recent studies have shown that central anatomical singlebundle ACL reconstruction can also restore normal knee function. [3][4][5] Several clinical studies have been performed which compare the single-bundle and double-bundle techniques but these have given conflicting results. 1,3,5,6 Restoration of normal biomechanical function is the primary goal of ACL reconstruction.…”
mentioning
confidence: 99%
“…As per previous studies, ACL reconstructions led to better clinical [2,10,16,24,28,38,40] and knee stability outcomes [1,5,7,19,20], but preoperative information on ACL anatomy is an essential prerequisite in determining optimal graft choice and restoring native ACL anatomy.…”
Section: Fig 3 Percentage Of the Length Of Tibial Acl Insertion Sitementioning
confidence: 74%